Studies on unidirectional grown L-proline lithium bromide an NLO material for optoelectronic applications. (2021) - Ramesh, G.; Uthrakumar, R.; Raja Saravanan, M.E.; Kumar, M.; Gobi, G.; Inmozhi, C.; Kaviyarasu, K.
Abstract: Bulk single crystal of L-Proline lithium bromide (LPLB) was successfully grown from aqueous solution by Sankaranarayanan-Ramasamy (SR) unidirectional growth method with dimensions of 10 mm diameter and 50 mm length. Single crystal X-ray diffraction studies has been carried out to confirm the crystalinity of the material. The optical absorption window and the cutoff wavelength of the LPLB have been identified by UV–vis–NIR studies. Dielectric studies have been carried out for the grown crystal. The mechanical asset of the grown crystal has been studied using Vicker's microhardness tester and the results were discussed in detail.